Boiling heat transfer with a microporous heating surface in a narrow gap with cover plates of different wettability - Rukhsar, Aqsa; Fadda, Dani; Lee, Jungho; You, Seung M. (International Journal of Heat and Mass Transfer, 2025)
An experimental study on boiling heat transfer with distilled water and a copper high-temperature thermally-conductive microporous coating (Cu-HTCMC) is performed in a narrow gap of 0.64, 1, 2, 3, and 5 mm thickness with hydrophilic and hydrophobic cover plates having apparent contact angles of 11°, 70°, and 150°. The parahydrophobic nature of the microporous copper coating and the interconnected channels within the coating allow the heating surface to stay wet and the boiling heat transfer performance to significantly exceed that of an uncoated copper surface. A hydrophobic cover plate causes stratified flow in the narrow gap, while a hydrophilic cover plate causes a laterally growing bubble in the gap. Regardless of the cover plate wettability, the wall superheat follows the unconfined case without any deterioration in the narrow gap up to the dryout heat flux due to the Cu-HTCMC on the boiling surface. Furthermore, minimal reduction in the critical heat flux is observed in narrow gap boiling with a hydrophobic cover plate, but significant reduction is observed with hydrophilic cover plates. The wettability effect diminishes as the gap size ≤ 1 mm since the vapor fills the narrow gap. For such gap sizes, the heat transfer coefficient enhancement is observed at low heat flux, followed by a sudden drop when vapor fills the gap and the surface struggles to stay wet.
Keywords: Boiling heat transfer; Cover plate; Cover plate wettability; Heating surfaces; Hydrophilics; Hydrophobics; Microporous; Microporous coatings; Narrow gap; Plate wettability; Boiling heat transfer; Cover plate wettability; Hydrophilic; Hydrophobic; Microporous coating; Narrow gap